Homocysteine, vitamin B12, and folate circulating levels in women with and without polycystic ovary syndrome: A systematic review and meta-analysis - Ulloque-Badaracco, Juan R. (2024)
Background: Some studies have reported that homocysteine, vitamin B12, and folic acid levels are associated with polycystic ovary syndrome (PCOS), whereas other studies yielded controversial results. Objectives: This study aimed to systematize the available evidence of homocysteine, vitamin B12, and folate levels in women with and without PCOS. Design: Systematic review and meta-analysis Data Sources and Methods: A systematic search without language restrictions was performed on PubMed, Ovid/Medline, Scopus, Embase, and Web of Science. In addition, the reference lists of the selected studies were reviewed. The Newcastle–Ottawa Scale was employed to evaluate the quality of studies. The means and standard deviations of the outcomes were pooled as standardized mean differences (SMDs) with 95% confidence intervals (CI). Furthermore, the DerSimonian and Laird method was employed for the quantitative synthesis. Results: A total of 75 studies met the eligibility criteria for at least one outcome. Patients with PCOS had higher circulating homocysteine levels than those without (SMD: 0.82; 95% CI: 0.62–1.02, n = 70 studies, p < 0.001). This trend remained in the sensitivity and subgroup analyses by world regions of studies, assay methods, and insulin resistance. No significant differences were observed in circulating vitamin B12 (SMD: −0.11; 95% CI: −0.25 to 0.03; n = 17 studies, p = 0.13) and folate levels (SMD: −0.2; 95% CI: −0.68 to 0.27; n = 17 studies, p = 0.41) between patients with and without PCOS. Conclusions: (i) Patients with PCOS exhibited significantly higher homocysteine levels than those without, and (ii) no significant differences were observed in both vitamin B12 and folate levels in women with and without PCOS. Registration: PROSPERO ID (CRD42023432883)